P293 What is the significance of a faecal elastase-1 level between 200 – 500μg/g?. (19th June 2022) - Fernandes, Darren; Fernandes, Darren; Andreyev, Jervoise
Abstract : Introduction: Pancreatic exocrine insufficiency (PEI) is a common cause of gastrointestinal (GI) symptoms relating to malabsorption. It is commonly diagnosed if Faecal elastase-1 (FE-1) levels are below 200μg/g. However, there is insufficient data to define the significance of faecal elastase levels above 200μg/g but less than 500μg/g, with a suggestion that levels between these values being a deviation from normal pancreatic exocrine function. This study therefore sought to assess the response to treatment in patients who had a FE-1 level between 200-500μg/g. Methods: This was a retrospective study that was approved by our local audit committee, audit registration L0448. Patient information was requested from the pathology laboratory at United Lincolnshire Hospitals NHS Trust for all FE-1 samples taken between April 2019 and March 2021. Those with results of <200 or >500 were excluded. Notes and medical records of those remaining were reviewed with any seen in an outpatient setting having their presenting symptoms recorded before trialling Creon. Subsequent clinic letters were then reviewed following commencement and a positive response noted if the initial symptoms responded to treatment. Results: 82 patients had a FE-1 result between 200-500. Ages ranged from 27 to 90 (median = 63). 78 were referred to the Gastroenterology department with a wide range of non-specific GI symptoms. 28 patients were given a trial of Creon. The dosing regime varied, with the majority being trialled on two capsules (50, 000 units) with meals and one capsule (25, 000 units) with snacks. Adjuvant treatment was given, with 8 taking multivitamins and 3 taking Proton Pump Inhibitors (PPIs). 20 patients showed an improvement in symptoms of diarrhoea, steatorrhoea and bloating. 3 patients did not tolerate Creon, developing nausea and vomiting and the remaining 5 showed no response. Conclusions: Our results show that clinicians should exercise caution when using defined reference ranges to diagnose PEI and provide treatment with PERT. Although it is often believed patients with PEI will only display symptoms when pancreatic function has dropped to <10%, there is now a consensus that these patients may instead demonstrate a graded response to reduced exocrine function and so will benefit from having earlier testing and treatment. Indeed, our findings support this suggestion, with nearly ¼ of patients with a FE-1 of between 200-500 showing a response following treatment with PERT.